Value at risk: teoría y aplicaciones - Johnson, Cristian (Estudios de Economía, 2016)
This article describes the Value at Risk concept, popularized during the last ten or fifteen years, presenting applications on stocks, bonds, interest and exchange rate forward contracts, and swaps. We applied asymmetric GARCH methodologies over Chilean stock indexes to enhance our risk evaluation performance. Liquidity adjusted Value at Risk methodologies for individual and multiple asset portfolios are discussed. To conclude, we applied this methodology to evaluate the performance in three Chilean financial institutions.